2012
DOI: 10.1007/s10620-012-2086-7
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Dysfunction in Chronic Pancreatitis

Abstract: Chronic pancreatitis (CP) is a progressive inflammatory disease characterized by irreversible destruction of pancreatic secretory parenchyma, fibrosis, exocrine atrophy, and endocrine insufficiency leading to diabetes. Secondary diabetes occurring in CP subsequent to destruction of pancreatic β-cells is distinct, since it involves β-cell dysfunction amidst an inflammatory milieu. Even though considerable knowledge is available on the pathophysiology and clinical management of CP, relatively much less is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 47 publications
1
57
1
3
Order By: Relevance
“…Although chronic pancreatitis is closely related to insulin insufficiency and diabetes mellitus (2), the molecular relationship between insulin secretion and chronic pancreatitis is unclear (17). This study demonstrates that CCR2-KO mice receiving long-term cerulein develop more severe chronic pancreatitis via 1) downmodulation of GLP-1R expression, 2) decrease in insulin release, and 3) hyperglycemia.…”
Section: Discussionmentioning
confidence: 78%
“…Although chronic pancreatitis is closely related to insulin insufficiency and diabetes mellitus (2), the molecular relationship between insulin secretion and chronic pancreatitis is unclear (17). This study demonstrates that CCR2-KO mice receiving long-term cerulein develop more severe chronic pancreatitis via 1) downmodulation of GLP-1R expression, 2) decrease in insulin release, and 3) hyperglycemia.…”
Section: Discussionmentioning
confidence: 78%
“…23,24 Patients often have transient pain relief, but due to the genetic defect there is diffuse involvement of the entire pancreas and pain eventually recurs in up to 50% of patients; 2530 exocrine and endocrine insufficiency often develops over time. 7,31 Total pancreatectomy (TP) eliminates the source of the pain, and potentially eliminates risk of pancreatic cancer in this HGP group patients and IAT prevents or minimizes TP- related diabetes. Based on this natural history, it has been our practice at the University of Minnesota to offer TP-IAT rather than partial resection or duct drainage procedures in this group of patients, if they meet our criteria for TP-IAT.…”
Section: Discussionmentioning
confidence: 99%
“…Both cystic fibrosis and chronic pancreatitis are conditions associated with a loss of pancreatic endocrine function after the exocrine dysfunction has become manifest. The pathophysiological mechanisms in these syndromes are intricate, involving beta cell failure and destruction secondary to chronic inflammation and fibrosis (51). Notably, a recent study reported an increase in MAPKdriven cytokines in the duodenal juice of CEL-MODY patients (52).…”
Section: Discussionmentioning
confidence: 99%